Erasmus+: A study of the path of pedagogical innovation practices - Araújo, Filipa Pereira (2023)
The main objective of this doctoral research is to identify/classify the nature of the pedagogical practices used and skills developed through the European Action Scheme for the Mobility of Students (Erasmus+) in secondary education. Methodologically, we used the qualitative method, focusing on exploratory-descriptive research through content analysis of a set of 12 articles, using NVIVO11 software. Preliminary conclusions show us that this program has been developing pedagogical innovation paths and practices based on active pedagogies and methodologies, with a particular focus on essential learning and intercultural education. The goal is to learn from each other and, together, learn to live together and become citizens for the world.